Stigma of infidelity associated with condom use explains low rates of condom uptake: qualitative data from Uganda and Tanzania - Kathryn Broderick; Christine Aristide; Brooke W. Bullington; Juliet Mwanga-Amumpaire; Jennifer A. Downs; Radhika Sundararajan (BMC, 2023)
Plain language summary Condoms are used to prevent HIV infection. Even though public health organizations have encouraged people to use condoms, many people in sub-Saharan Africa do not, especially in sexual encounters with someone that they are living with or married to. In this study, we wanted to understand the reasons that people were not using condoms. Between 2016 and 2019, we spoke with individuals in Uganda in one-on-one interviews about HIV prevention and testing and with focus groups in Tanzania about family planning. We analyzed transcripts of these conversations to find common themes about people's impressions of condom use. We learned that many of our participants believed that abstaining from sex and being faithful were the best ways to prevent HIV infection, but that they were not realistic strategies in the long term. Condoms were thought of as a useful tool for prevention when you "fail" at abstinence and monogamy. They were linked with being unfaithful, so people did not feel comfortable suggesting their use in committed relationships. These findings show that the "ABC" strategy for HIV prevention education may be continuing to make people think negatively about condom use. This strategy presented a tiered approach to HIV prevention, telling people it was best to (A) abstain, (B) be faithful to one's partners, and (C) use a condom. In order to increase engagement with HIV prevention, public health messages need to acknowledge the negative associations between condoms and infidelity.